China Past forward - forever Beijing : / ( video recording ) - Liu Chang; Randle , Jim. (China)
Not too far from the Forbidden City, Beijing secret treasures are slowly vanishing. The famous "Hutongs" or alleys and "siheyuan" or courtyard houses dating as far as the 12th century are under threat from developers. These served as traditional homes to the bureaucracies that served the various Chinese empereror. Even today some of these families continue to live in the "Hutongs". These programs capture the dilemmas, contemporary or otherwise, faced by a society/people undergoing rapid change in their new century.